Study on APP Design of Assisting New Immigrant Women with Healthcare Communication - Fang-Suey Lin; Lu-Zhen Xu; Yi-Tung Liu (Journal of Management Practices, Humanities and Social Sciences, 2017)
The main purpose of this study is to develop an interactive medical communication board that would be adaptable both in terms of language and metaphor. This board would be tested on diverse population to assess its efficacy in clinical diagnosis to help new female immigrants and their children. Therefore, this study intends to develop an assistive visualization tool of medical communication to achieve the objective of friendly communication among foreign spouses, ill children, and medical service. This research project focuses on integrating medical and design professional fields to develop medical information and auxiliary communication tool, as well as to design doctor-patient communication APP prototype concept. Design draft and discussion with users were conducted. The study mainly adopted interviews, observations, and User Experience Innovation Design (UXID) to carry out interviews with 24 Vietnamese and Indonesian new immigrant women. These firsthand practical data were then transcribed and sorted out. By designing an APP prototype, researchers finally achieved the purpose of assisting new immigrant women in seeking health care and expressing their symptoms. This study is a pioneer study in health communication for immigrants and it can also serve as a reference for other follow-up studies.